The place of anthropologist’s belief (or not) at the field (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
While participating in some ceremonies in so-called shamanic contexts, I was faced with a dilemma: how to give anthropological meaning to seemingly extraordinary experiences, such as the vision of death? How to respond to fellow anthropologists who kept asking me: did you really see death? And, most importantly, how to respond without falling into the false opposition of the anthropologist’s belief against the native’s belief? In other words, without mobilizing the problematic concept of belief, but rather problematizing my colleagues’ own question. After all, what are the reasons that support such questioning? In this article, I briefly present the context of such practices that I was invited to participate with my own body. When putting my body to the test in practices that are commonly so physically hard, I looked for support in theories that can dialogue with such experiences, mainly phenomenology and its concern for the sensitive dimension of the experience that develops with the body as a gateway to the world. Finally, what mattered about these experiences, as I try to argue by mobilizing the affective turn, is not to believe or not in the vision of death, but to show how it affected me and to seek to set that affect in motion.
Keywords: Shamanism; Red Road; Affective Turn; Belief; Experience